2015
DOI: 10.1007/s00766-015-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

Workshop videos for requirements communication

Abstract: Abstract-Shared understanding of requirements between stakeholders and the development team is a critical success factor for requirements engineering. Workshops are an effective means for achieving such shared understanding since stakeholders and team representatives can meet and discuss what a planned software system should be and how it should support achieving stakeholder goals. However, some important intended recipients of the requirements are often not present in such workshops: the developers. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Karras et al [11] highlight the benefit of videos to capture verbal and nonverbal information comprehensively. Jirotka and Luff [12], as well as Fricker et al [13], emphasize the usefulness of videos as a stable reference for post-processing work. Developers can retrieve more details from a video than from any written documentation [14].…”
Section: Introductionmentioning
confidence: 97%
“…Karras et al [11] highlight the benefit of videos to capture verbal and nonverbal information comprehensively. Jirotka and Luff [12], as well as Fricker et al [13], emphasize the usefulness of videos as a stable reference for post-processing work. Developers can retrieve more details from a video than from any written documentation [14].…”
Section: Introductionmentioning
confidence: 97%
“…In the model presented in this study, no relationship has been proposed between the quality constructs, but one might try, for example, to investigate if a system that improves adherence also changes user attitudes about its contribution to effectiveness. However, considering that only recursive relationships can be used in the PLS-SEM models, we cannot investigate the circular impact between qualities and satisfaction with this technique [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…The adequate use of documentation for communication is one challenge in requirements engineering (RE) [4]. In recent years, several researchers [3,5,8] addressed this challenge by using videos as a communication mechanism. All of them concluded that this way of using videos has the potential to facilitate requirements communication.…”
Section: Introductionmentioning
confidence: 99%